The Intersection of 'Community' within the Reading Experience: Lesbian Women's Reflections on the Book as Text and Object - Pecoskie, Jennifer L. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Using the qualitative methods of interviewing and narrative gathering, this research examines ideas of socially interconnected reading practices and focuses on meanings of community in the lives of adult lesbian women who read for pleasure. It is argued that reading is a useful means to understanding ‘information’ and the everyday lives of readers. En utilisant les méthodes qualitatives de l’entrevue et de la collecte narrative, cette recherche examine les idées des pratiques de lecture socialement interconnectées et converge sur la signification de la communauté dans la vie des femmes lesbiennes adultes qui lisent pour leur loisir. On soutient que la lecture est un moyen utile pour comprendre « l’information » et la vie quotidienne des lecteurs. ***Student to CAIS/ACSI Award Winner***